Stimulating the Learning of Polish and Czech Students with the Use of e-Learning Resources - Ogrodzka-Mazur, Ewa; Szafrańska, Anna; Malach, Josef; Chmura, Milan (Wydawnictwo Naukowe UAM, 2018)
The article is a result of the collaboration between Polish and Czech scientists who explore the issues of applying the resources from e-learning environment by academic teachers. The presented studies were conducted in 2015-2016 within the IRNet project – International research network for study and development of new tools and methods for advanced pedagogical science in the field of ICT instruments, e-learning and intercultural competences in Poland (University of Silesia in Katowice, Faculty of Ethnology and Educational Science in Cieszyn) and the Czech Republic (University of Ostrava, Pedagogical Faculty). The undertaken research was aimed at learning the opinions of academic teachers on their preparation for distance classes and for the stimulation of students’ learning process. In the studies, the constructivist perspective was applied, which highlighted (in the educational process) the learner’s activity resulting in the subject builds their educational reality. What was referred to due to the comparative nature of the research was Harold J. Noah’s model of comparing the quality of University education. The cases of Poland and the Czech Republic were discussed.
Stymulacja nauki polskich i czeskich uczniów za pomocą narzędzi e-learningu
Keywords: upper education didactics; academic teachers; stimulation of the learning process; e-learning resources; comparative studies